Valuation on characteristics in the milk market - Falkdalen, Maria (2017)
The total number of milk cows in Sweden is decreasing and at the same time the market for plant based milk made of oat, almond, and soy beans is expanding. Society provides easy access to information and the choices of what to buy and eat are numerous. The need of understanding the market demand, how prices are determined and what factors are affecting the prices are therefore highly relevant and interlinked topics. This thesis will therefore estimate a price function for fresh milk in Sweden with the aim of determining the willingness to pay for plant based milk and to see if and in that case, how much, socioeconomic and demographic variables are influencing the milk price. A hedonic price model is applied using household scanner data from the year 2011. The results from the regression show that the willingness to pay for plant based milk is 32 % higher than the average milk price and the variable urban has a price premium of 4,3 %, indicating that the average price of milk is 4,3 % higher in urban areas, compared to rural areas. The results from the study give incentives for future research to further investigate the determinants of the milk price and the reasons behind the consumers’ demand.